State-of-the-art review: Reduction factor of traditional steel moment resisting, braced or eccentrically braced systems. (January 2022) - Hassan, Maha M.
Abstract: This paper presents state-of-the-art review of force reduction factor evaluation for the main traditional steel lateral load resisting systems: moment resisting frames, concentrically braced frames, and eccentrically braced frames. Force reduction factor represents one of the major key factors in force-based design of structures. Its value greatly affects forces considered in design and subsequently member sizes. Historical background will first be explored. Afterwards, different experimental and numerical research efforts shall be summarized. Reduction factor values in different design codes are investigated and compared. The work is intended to summarize the available research efforts and showcase the missing areas that still need investigation.